1999
DOI: 10.1097/00006842-199905000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Endocrine Alterations After Masturbation-Induced Orgasm in Women

Abstract: Sexual arousal and orgasm produce a distinct pattern of neuroendocrine alterations in women, primarily inducing a long-lasting elevation in plasma prolactin concentrations. These results concur with those observed in men, suggesting that prolactin is an endocrine marker of sexual arousal and orgasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 70 publications
8
92
0
3
Order By: Relevance
“…Rowland et al (1987) reported some increase in PRL while watching erotic videos; Carani et al (1990b) found no increase. In contrast, in a recent series of studies in which masturbation or sexual activity with a partner led to orgasm or ejaculation, a clear increase in PRL was observed following orgasm in both men (Kruger et al 1998(Kruger et al , 2003a and women (Exton et al 1999), with levels still raised after 60 min. This pattern was not found in a parallel study of men who masturbated without ejaculating (Kruger et al 2003b).…”
Section: Peptidesmentioning
confidence: 60%
See 1 more Smart Citation
“…Rowland et al (1987) reported some increase in PRL while watching erotic videos; Carani et al (1990b) found no increase. In contrast, in a recent series of studies in which masturbation or sexual activity with a partner led to orgasm or ejaculation, a clear increase in PRL was observed following orgasm in both men (Kruger et al 1998(Kruger et al , 2003a and women (Exton et al 1999), with levels still raised after 60 min. This pattern was not found in a parallel study of men who masturbated without ejaculating (Kruger et al 2003b).…”
Section: Peptidesmentioning
confidence: 60%
“…So far, no changes in plasma levels of -endorphin have been found during sexual arousal or orgasm in men (Kruger et al 1998) or women (Exton et al 1999). The possible relevance of -endorphin to the postejaculatory refractory state will be considered below, together with PRL.…”
Section: Peptidesmentioning
confidence: 97%
“…Mating-or sexual intercourse-induced PRL secretion seems to be similar in rodents and humans (Kamel et al 1975, Kruger et al 1998, Exton et al 1999. In addition, in rats, a specific release pattern is switched on after mating with PRL surges during early morning and late afternoon as outlined above .…”
Section: Pregnancymentioning
confidence: 83%
“…4; Exton et al 2001). This effect was not observed during sexual arousal per se (Kruger et al 1998, 2003a, Exton et al 1999, 2000. Furthermore, the magnitude of the PRL increase following intercourse was 400% greater than following masturbation, which may indicate the biological significance of cervicovaginal stimulation and/or physical contact with a partner (Brody & Kruger 2006).…”
Section: Sexual Behavior and Reproductionmentioning
confidence: 93%
“…It is important to note that our study assessed symptoms occurring post-coitally (with or without experienced orgasm) and not specifically after orgasm, hence do not cover a post-orgasmic condition. Given the hormonal changes that happen at the time of orgasm, which tend to be different from sexual excitement, this could be important (Exton et al, 1999;Krueger et al, 2003). To address this issue we conducted post-hoc analysis using a questionnaire sent to the twins in 2008 and asking about frequency of orgasm during intercourse.…”
Section: Discussionmentioning
confidence: 99%